2010
DOI: 10.2189/asqu.2010.55.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Stealthy Footsteps to the Boardroom: Executives' Backgrounds, Sophisticated Interpersonal Influence Behavior, and Board Appointments

Abstract: Drawing from theory and research on interpersonal attraction, as well as interviews with 42 directors of large U.S. industrial and service fi rms, we identifi ed a set of social infl uence tactics that are less likely to be interpreted by the infl uence target as manipulative or political in intent and are therefore more likely to engender social infl uence. We consider who among top managers and directors of large fi rms is most likely to exercise such tactics and how their use affects the likelihood of garne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 105 publications
6
120
1
2
Order By: Relevance
“…Our theory and findings complement a recent study by Stern and Westphal (2010), which demonstrated that ingratiatory behavior by top managers and directors was more successful to the extent that it included relatively sophisticated forms of flattery, such as framing flattery as advice seeking. Stern and Westphal (2010) suggested that these behaviors, though they involve exaggerated praise, are relatively subtle and thus less likely to be recognized as insincere.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our theory and findings complement a recent study by Stern and Westphal (2010), which demonstrated that ingratiatory behavior by top managers and directors was more successful to the extent that it included relatively sophisticated forms of flattery, such as framing flattery as advice seeking. Stern and Westphal (2010) suggested that these behaviors, though they involve exaggerated praise, are relatively subtle and thus less likely to be recognized as insincere.…”
Section: Discussionsupporting
confidence: 80%
“…In a recent study, Stern and Westphal (2010) showed that ingratiatory behavior by top managers and directors was more likely to engender social influence to the extent that it was comprised of relatively subtle or sophisticated behaviors, such as framing flattery as advice seeking, or framing a compliment as likely to make the influence target uncomfortable. Although effective in general, such tactics are unlikely to resolve the ingratiator's dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even though boards and compensation committees should push back and correct biases initiated or supported by the CEO (Shleifer and Vishny 1997, Iliev et al 2015, Dicks 2012, there are various reasons why that may not be the case. For example, board members have incentives to maintain cordial social relations with the CEO (Gulati and Westphal 1999, Khurana 2011, Stern and Westphal 2010. Also, board members are often executives in their own right, and biased peer groups provide an indirect justification for a rise in their own compensation (Westphal and Zajac 1995).…”
Section: The Principles Of Compensation Benchmarking 21 Bias In Commentioning
confidence: 99%
“…Some persons are more conflict avoiding than others. From the work of Westphal andStern (2006, 2007), Stern and Westphal (2010), we know that personality traits such as opinion conformity and a tendency to use flattery are beneficial to individual board members because it increases the chances of receiving board appointments. The tendency to appoint and retain conforming, non-critical board members with similar views (Westphal and Zajac 1995)-even when they are demographically different (Zhu et al 2014)-can be an important driver for conflict avoidance.…”
Section: An Extended Model Of Conflict In the Boardroommentioning
confidence: 99%